Aging safely in Alentejo – understanding for action - preventing falls and violence against older people: study rationale, aims, design, and preliminary results - Catarina Pereira; Jorge Bravo; Gorete Reis; Felismina Mendes (BMC Public Health)
Abstract Background Falls and violence against older people might represent a joint public health problem, as both may result in injury, fear, social isolation, sedentary behavior and dependence or even death. The ESACA project “Aging safely in Alentejo - Understanding for action” was designed to promote the healthy aging of older people in Alentejo by preventing the occurrence of falls and violence. This study aimed to report the ESACA protocol and the preliminary outcomes. Methods The ESACA study has a twofold design as a cross-sectional study that included retrospective and prospective surveys. The participants were 508 community-dwelling older people. Assessments included falls, the risk of violence against older people, sociodemographic characteristics, health-related measurements, fear of falling, anthropometric measures and body composition, functional physical fitness, physical activity, and environmental hazards. Results Among the participants, 43% were fallers, 21% were recurrent fallers, and 22% were victims of one or more kinds of violence (psychological: 17.1%, physical: 5.6%, and patrimonial: 3.0%). Moreover, the cumulative results suggested high risk on several risk factors for falling (7 factors: 0.6% to 2 factors: 17.4%) and of  violence (26.7%). Conclusions In the ESACA project, a wide range of potential influencing factors on falls and violence risk factors were measured, and comprehensive quality control measures were applied. Overall, the results suggest that for falls and violence prevention strategies to be effective, it is essential to evaluate, diagnose, and inform all stakeholders in a directed and useful way. Moreover, we believe that our project outcomes may help change mindsets and behaviors by involving people in active aging and well-being programs that promote exercise and avoid isolation.